1997
DOI: 10.1016/s0014-5793(97)01164-2
|View full text |Cite
|
Sign up to set email alerts
|

Disturbed progastrin processing in carboxypeptidase E‐deficient fat mice

Abstract: The fat mouse strain exhibits a late-onset obesity syndrome associated with a mutation in the gene encoding carboxypeptidase E (CPE). Since CPE plays a central role in the biosynthesis of a number of regulatory peptides, including gastrin, we examined the biogenesis and processing of progastrin in fatlfat mice by measuring gastrin mRNA, carboxyamidated gastrin and its processing intermediates in the stomach. The tissue concentration of carboxyamidated (i.e. bioactive) gastrin was only slightly reduced (601 ± 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 34 publications
3
25
1
Order By: Relevance
“…We demonstrate that antropyloric gastrin cells are strongly positive for CPE. This agrees with previous data showing that CPE-deficient mice have impaired gastrin processing (Gomez et al 1999;Lacourse et al 1997;Udupi et al 1997). Similarly, our data show that antropyloric somatostatin-producing D cells do not contain detectable levels of CPE.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We demonstrate that antropyloric gastrin cells are strongly positive for CPE. This agrees with previous data showing that CPE-deficient mice have impaired gastrin processing (Gomez et al 1999;Lacourse et al 1997;Udupi et al 1997). Similarly, our data show that antropyloric somatostatin-producing D cells do not contain detectable levels of CPE.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, although data on CPEdeficient fat mice suggest a role for CPE in gastrin processing (Lacourse et al 1997;Udupi et al 1997), it has never been determined whether CPE is present in these cells. Moreover, fat/fat mice also have perturbed somatostatin levels (Friis-Hansen and Rehfeld 2000).…”
Section: Introductionmentioning
confidence: 99%
“…22 Fully processed gastrin in the Cpe fat/fat mouse stomach was reported to be decreased by 65% in one study 23 and by 16% in another. 24 Several of these studies examined the levels of C-terminally extended precursors and found relatively high levels of these processing intermediates in the Cpe fat/fat mouse tissues and either little or no detectable levels of these intermediates in wild-type mouse tissues. A limitation of these previous studies is the radioimmunoassay used to detect the peptides.…”
Section: Introductionmentioning
confidence: 99%
“…These mice lack carboxypeptidase E activity due to a point mutation within the coding region of the gene [Naggert et al, 1995], but are still able to carry out a reduced amount of neuroendocrine peptide processing [Naggert et al, 1995;Fricker et al, 1996;Rovere et al, 1996;Cain et al, 1997;Lacourse et al, 1997;Udupi et al, 1997]. CPD has carboxypeptidase E-like enzyme properties, but differs in several respects.…”
mentioning
confidence: 99%